Fibromialgia: chi deve rimodulare la percezione del dolore in questi pazienti? - S. Stisi; F. Atzeni; P. Sarzi- Puttini; M. Cazzola (PAGEPress Publications, 2011)
Fibromyalgia (FM), a poorly-understood chronic condition, is characterized by widespread musculoskeletal pain, fatigue, non-restorative sleep, psychological distress, and specific regions of localized tenderness, all in the absence of otherwise apparent organic disease (1). While the etiology of FM is unclear, accumulating data suggests that disordered central pain processing likely plays a role in the pathogenesis of symptoms (2). Although various pharmacological treatments have been studied for treating FM, no single drug or group of drugs has proved to be particularly useful in treating FM patients as a whole; and to date, only two drugs (pregabalin and duloxetine) have earned U.S. Food and Drug Administration (FDA) approval for treating the syndrome in the United States (USA) (3, 4)...